Ambiguity of Humor Discourse in Indra Frimawan Content in Comika.id - Raharja, Rio Slamet; Dewi, Trie Utari (Universitas Nusantara PGRI Kediri, 2025)
Ambiguity poses a significant challenge in communication, often causing misinterpretation or confusion in message decoding. The resulting lack of clarity can obstruct effective information transfer, as recipients may derive meanings different from the speaker’s intent. This qualitative descriptive study aims to identify and analyze specific forms of lexical ambiguity and grammatical ambiguity in Indra Frimawan's comedy content on the comika.id platform. The methodology focuses on analyzing humorous discourse related to ambiguity phenomena. The semantic approach is essential, playing a crucial role in the precise understanding and proper use of language through in-depth analysis of semantic meaning. Findings indicate 19 distinct forms of lexical ambiguity and 20 forms of grammatical ambiguity. Grammatical ambiguity is further categorized into 13 instances of temporary ambiguity and 7 instances of permanent ambiguity. This suggests that Indra Frimawan’s signature humorous style, which deliberately employs ambiguous wording, is an effective and unique means of entertaining the audience. It also provides a distinctive comedic blueprint for other stand-up comedians to explore. The study contributes to the understanding of intentional linguistic ambiguity as a source of humor.